2019
DOI: 10.1039/c9ob01402k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and glycosidase inhibition of conformationally locked DNJ and DMJ derivatives exploiting a 2-oxo-C-allyl iminosugar

Abstract: The synthesis and glycosidase inhibition profile of a series of bicyclic analogs of DNJ and DMJ displaying a similar hydroxyl pattern and a distinct conformation is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
6
0
1
Order By: Relevance
“…Moreover, the reduction of carboxylic acid derivatives, and more particularly of amides, by zirconium hydrides is a matter of strong interest. These transformations can indeed be achieved with remarkable chemoselectivity, and involve intermediates having a versatile reactivity. , However, to the best of our knowledge, the reduction of CO bonds by zirconium hydrides has never been achieved with the main group metal hydride used as the stoichiometric reductant and a catalytic amount of zirconium complex . In this context, we recently reported that a mixture of Cp 2 ZrCl 2 and DIBAL-H in tetrahydrofuran (THF) induce the selective de- O -acetylation of the primary position of peracetylated compounds on a broad scope of polyfunctional substrates (Scheme a) .…”
Section: Introductionmentioning
confidence: 86%
“…Moreover, the reduction of carboxylic acid derivatives, and more particularly of amides, by zirconium hydrides is a matter of strong interest. These transformations can indeed be achieved with remarkable chemoselectivity, and involve intermediates having a versatile reactivity. , However, to the best of our knowledge, the reduction of CO bonds by zirconium hydrides has never been achieved with the main group metal hydride used as the stoichiometric reductant and a catalytic amount of zirconium complex . In this context, we recently reported that a mixture of Cp 2 ZrCl 2 and DIBAL-H in tetrahydrofuran (THF) induce the selective de- O -acetylation of the primary position of peracetylated compounds on a broad scope of polyfunctional substrates (Scheme a) .…”
Section: Introductionmentioning
confidence: 86%
“…The purification on silica gel (eluent hexanes/AcOEt: 50/50) afforded the desired exo compound but the minor endo one was not isolated after flash chromatography. MS (EI) m/z (%) 319 (14), 304 (20), 289 (23), 288 (91), 261 (23), 244 (93), 213 (26), 212 (20), 186 (66), 170 (25), 168 (100), 158 (26), 144 (27), 132 (45), 130 (57), 91 (87), 77 (35), 43 (49).…”
Section: Characterization Of the Obtained Acetonidesmentioning
confidence: 99%
“…9 Therefore, numerous syntheses of iminosugars have been developed to improve the potency and selectivity of these inhibitors but also to better understand the structure-activity relationships. 1c, 10 The influence of ring size and rigidity have been studied through the synthesis of 4-membered, 11 5-membered 12 and 7-membered rings, 13 through bicyclic locked deoxy-iminosugars, 14 hydrazine type bicyclic iminosugars 15 , constrained fused bicyclic iminosugars 16 or sp 2 -iminosugars. 17 Many of the reported syntheses use carbohydrates as starting materials 18 including stannylated ones 19 but others start from simple organic molecules.…”
Section: Introductionmentioning
confidence: 99%
“…[21] Aktivitas antihiperglikemik DNJ melalui penghambatan absorbsi dan pencernaan dari maltosa yang terdapat dalam kandungan beras. [22] DNJ bekerja dengan mengubah ekspresi transpor Na + /K + -ATP, SGLT1 dan GLUT2 yang banyak diekspresikan di saluran usus. DNJ akan mengurangi penyerapan jumlah glukosa yang dikonsumsi dan mengkatalis reaksi glikolisis dan glukoneogenesis dari metabolisme glukosa yang ada di hepar melalui peningkatan glukokinase (GK), phosphofructokinase (PFK), pyrivate kinase (PK), phosphoenolpyruvate carboxykinase (PEPCK) and glucose-6-phosphatase (G-6-Pase).…”
Section: Bahasan Patogenesis Infeksi Virus Dengueunclassified